Transitions into adulthood for children with a severe intellectual disability: parents' views - Biswas, Sanchia Rima (2015)
Introduction: Despite a growing body of intellectual disabilities literature around the transition into adulthood, most studies have focused upon physical aspects of the transition e.g. from school to employment or into adult services. My study sought to explore the transition into adulthood from a developmental/lifecourse perspective in order to address this current gap within the literature. Given that parents are often regarded as primary witnesses to their child’s transition into adulthood, their views were explored in order to access knowledge around this particular transition.